2004
DOI: 10.1177/0898010104264778
|View full text |Cite
|
Sign up to set email alerts
|

Men of Prayer: Spirituality of Men With Prostate Cancer

Abstract: Spirituality plays a powerful role in cancer treatment and recovery; it has been identified by hospitalized patients as one of their top priorities of care. However, health care providers struggle to find ways to address the spirituality of their patients. The purposes of this study were to discover what spirituality means for men with prostate cancer and how it influences their treatment. Eleven men, ages 54 to 71, with prostate cancer were interviewed within several days following radical prostatectomy with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
54
1
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(62 citation statements)
references
References 28 publications
5
54
1
2
Order By: Relevance
“…Past research with cancer survivors have used the grounded theory approach to study spirituality [54,55]. Grounded theory is a systematic methodology that builds theory from data, rather than beginning the research process with clearly articulated hypotheses to prove [51].…”
Section: Recruiting Participantsmentioning
confidence: 99%
“…Past research with cancer survivors have used the grounded theory approach to study spirituality [54,55]. Grounded theory is a systematic methodology that builds theory from data, rather than beginning the research process with clearly articulated hypotheses to prove [51].…”
Section: Recruiting Participantsmentioning
confidence: 99%
“…These journeys illustrated comforting, as well as painful aspects. Cancer may provide an opportunity for spiritual growthregardless of prior spiritual or religious beliefs (Baldacchino & Draper, 2001;Walton & Sullivan, 2004).…”
Section: Breast Cancer and Spiritualitymentioning
confidence: 99%
“…Findings analyzed within the context of meaning making indicated that participants viewed spirituality and religion as helping them to have a spiritual surrender, accept reality, grow as people, see their purpose and destiny, overcome limitations, learn life lessons, build character and act in accord with their moral values, and trust in a higher power. In a similar qualitative investigation, Walton and Sullivan [19] identified three spiritual themes among men coping with prostate cancer: prayer, coping with cancer and support.…”
Section: Role Of Spirituality In Cancer Copingmentioning
confidence: 99%